2D skeleton extraction based on heat equation. (August 2018) - Gao, Fengyi; Wei, Guangshun; Xin, Shiqing; Gao, Shanshan; Zhou, Yuanfeng
Highlights: A heat surface is generated to approximate the real distance field, then extract the ridge lines of the heat surface as the output skeleton. A stable and noise-insensitive skeleton is computed directly. The extracted skeletons by the proposed method meet all the following properties at the same time, i.e. preserving topology, avoiding pruning and being free of user-specified parameters. Graphical abstract: Abstract: Object skeleton is a useful geometric tool for shape analysis tasks. It encodes the topological structure of the primitive shape and preserves a geometric cue as well. Skeletonization is a seemingly simple but difficult research problem. A desirable skeletonization algorithm has to be topologically complete, insensitive to boundary noise, without any branch pruning and free of user-specified parameters. In this paper, we propose a novel method based on the heat equation to extract skeletons assuming that the input is a binary image. Based on the connection between the skeleton and ridge lines, we use the smooth heat diffusion height surface to approximate the real distance field, and then extract the ridge lines of the surface as the output skeleton. Different from the existing approaches, the proposed method in this paper has the above-mentioned excellent properties and can capture the clean and stable skeleton directly. Extensive experimental results show that the new approach can yield better skeletons than the state-of-the-art.